The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.brainres.2014.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of anthocyanin- and proanthocyanidin-rich extracts in cellular models of Parkinson׳s disease

Abstract: Neuropathological evidence indicates that dopaminergic cell death in Parkinson’s disease (PD) involves impairment of mitochondrial complex I, oxidative stress, microglial activation, and the formation of Lewy bodies. Epidemiological findings suggest that the consumption of berries rich in anthocyanins and proanthocyanidins may reduce PD risk. In this study, we investigated whether extracts rich in anthocyanins, proanthocyanidins, or other polyphenols suppress the neurotoxic effects of rotenone in a primary cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 71 publications
6
140
1
4
Order By: Relevance
“…These results indicate that anthocyanins are the major contributor to the total antioxidant capacity of S. nigrum fruit, which is consistent with previous reports [25,26]. Until now, most anthocyanins extraction and purification have been carried out from blueberries or blackcurrants but not from S. nigrum fruits, and the purities were all almost below 40% [16,17], which were also lower than our result of purified anthocyanins from S. nigrum fruits. These evidences ensured that our purification method provided a fair chance of extracting anthocyanins from S. nigrum fruits with no change in compositions but a large increase in purity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that anthocyanins are the major contributor to the total antioxidant capacity of S. nigrum fruit, which is consistent with previous reports [25,26]. Until now, most anthocyanins extraction and purification have been carried out from blueberries or blackcurrants but not from S. nigrum fruits, and the purities were all almost below 40% [16,17], which were also lower than our result of purified anthocyanins from S. nigrum fruits. These evidences ensured that our purification method provided a fair chance of extracting anthocyanins from S. nigrum fruits with no change in compositions but a large increase in purity.…”
Section: Discussionsupporting
confidence: 92%
“…The purification of anthocyanins was investigated in different studies with different procedures. Strathearn et al (2014) [16] increased the purity of anthocyanins extracts to 20.6% after an enrichment step in a C18 solid-phase extraction of blueberries. Liu et al (2012) [17] utilized an Amberlite XAD-7 column and a Sephadex LH20 column to obtain a 31% purity of anthocyanins crude extracts of blueberries.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of rotenone, a potent rotenoid used in insecticides, has been used as a model of Parkinson's disease; it has been shown to result in the systemic inhibition of mitochondrial complex I activity, which leads to the degeneration of dopaminergic neurons within the substantia nigra and striatum (Yang et al, 2006). Chinese mulberry (Morus alba) extract rich in anthocyanins and proanthocyanidins is able to alleviate neurodegeneration in PD via enhancement of mitochondrial function (Strathearn et al, 2014). Other study revealed that an oxyresveratrol (oxy) a polyhydroxylated stilbene -rich mulberry extract alleviated rotenone neurotoxicity in primary midbrain cultures and attenuated neuronal cell death triggered by PD-related insults in cellular or animal models (Khan et al, 2010).…”
Section: Mulberry Extarct and Parkinson Diseases (Pd)mentioning
confidence: 97%
“…Using the cellular model of PD, Strathearn et al demonstrated that substances that are rich in anthocyanins might protect neurons from degeneration [24]. Sikorska et al documented similar observations regarding the beneficial effects of antioxidants on the inhibition of neurodegenerative processes [25].…”
Section: Discussionmentioning
confidence: 64%